Vision analysis of arges county farmers intend to associate and for what purpose - Marius Mihal Micu; Valentina Tudor (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
This paper aims to present an outlook for agriculture in terms of vision Arges county farmers. This paper will disseminate only part of the information obtained using two types of questionnaires in Arges county. The first questionnaire was applied farm representatives with legal form and the individual holdings without legal form and the second was applied forms of association representatives. The first purpose of applying the questionnaire was to identify opinion of farmers depending on the legal form of its intention to join, a second purpose is why farmers were intending to associate Taking into account the legal form of holdings and landform located where to be found, also sought the opinion of farmers on possible advantages they can get through their association. Observe farmers desire to enter into a form of association (85%), the existence of associations representing an important milestone in the growth of production and hence the profitability of farms and for which evidence is to supply. Analyzing parallel views of farmers, the benefits that you can get for joint association forms and forms of association presidents opinion on the benefits that farmers can get them in combination, it is found that in both cases the flagship advantage is the increased ability to promote products.
Keywords: 330; association; forms of association; agricultural producers; questionnaire; Arges county